Synthesis of Some Novel Quinazolino-Triazine Derivatives for Their Antimicrobial Activity - Namdeo, K P; Yaduvansi, Phool Singh; Bodakhe, S H (Current Research in Pharmaceutical Sciences, 2012)
A new series of 2,4,6-Trisubstituted- quinazolinone -s-Triazine designed and synthesized to meet the structural requirements essential for antimicrobial properties. 2,4,6-Trisubstituted- quinazolinone -s-Triazine were synthesized using anthranilic acid as a starting material. All the synthesized compounds were screened for antibacterial and antifungal activity on agar plates using neutrient broth (antibacterial) and Saboraud’s medium (antifungal ) by Cup-plate technique. The bacterial culture were E. coli, P. Fluorescens, S. Aureus, B.subtilis, fungal cultures were C. albicans, A. niger. The standard drugs used for the present study were Ciprofloxacin and Fluconazole as antibacterial and antifungal respectively. The synthesized compounds exhibited significant antibacterial as well as antifungal activity comparable to the standard drugs. Among these synthesized compounds, compound code PS3 showed maximum activity.